PENGARUH PROFITABILITAS, DIVIDEND PAYOUT RATIO, DEBT TO EQUITY RATIO, DAN NILAI PERUSAHAAN TERHADAP INCOME SMOOTHING PADA PERUSAHAAN FOOD & BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA - RIKA NOVIANTI; LEWI MALISAN; SALMAH PATTISAHUSIWA (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2016)
Income smoothing is an effort in controlling earning management to increase or decrease the company’s earning to reduce fluctuations in earnings. The purpose of this study was to examine the effect of profitability, dividend payout ratio, debt to equity, and firm value to income smoothing at Food and Beverage Companies listed on Indonesian Stock Exchange during 2010-2015. Eckel index used to classify companies that do or do not practice income smoothing. The variable used in this study is profitability proxies by ROA, dividend payout ratio, debt to equity ratio, and firm value is proxies by Price to Book Value (PBV). Population in this study was Food and Beverage Companies listed on Indonesian Stock Exchange during 2010-2015. Based on purposive sampling method, there were 8 of 14 Food and Beverage Companies that matched with the sample In the logistic regression analysis for the four independent variables, only variables of Profitability proxies by ROA that have a significant effect on the practice of income smoothing. While the dividend payout ratio, debt to equity ratio, and firm value does not significantly innfluence the practice of income smoothing.Keyword: Profitability, Dividend Payout Ratio, Debt To Equity Ratio, Firm Value, Income Smoothing.